TAMTSIL AL-HUWIYYAH WA AT-TAHMISY FI SYI’R AS-SALAMU ’ALAIKUM LI ANIS CHOUCHÈNE - Dzurrotul Qomariyah; Nur Hasaniyah; Ummi Hasanah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to analyze the representation of identity and marginalization in Anis Susan’s poem